Celebrar lo imposible El Código Civil en el régimen jurídico de la propiedad: Córdoba entre fines del siglo XIX y comienzos del XX - Cacciavillani, Pamela Alejandra (Global Perspectives on Legal History, 2021)
This book offers a legal-historical examination of the construction of property in the province of Córdoba, Argentina, at the end of the 19th century. The author analyzes the interaction of the civil codification, Argentina's federal structure, and the systems for the official surveying of land and registration of property. In this context, she focuses on the privatization of the territories belonging to indigenous communities in Córdoba province from the 1870s to the early 20th century.